Persentase remaja pengguna rokok pada klien klinik napza di Rumah Sakit Umum Pusat Sanglah Denpasar - Ade Purnamasari; Ni Ketut Sri Diniari; Anak Ayu Sri Wahyuni (Intisari Sains Medis, 2019)
Introduction: Smoking is a major cause of preventable death worldwide, and is a major risk factor for six of the eight leading causes of death, namely ischemic heart disease, cerebrovascular disease, lower respiratory infections, chronic pulmonary obstructive disease, tuberculosis and lung cancer. This study aims to determine the percentage of cigarette use, the characteristics of age for the first time smoking, and the percentage of use of cigarettes, alcohol, and other substances in PTRM Sandat clients Sanglah Hospital.Method: This study was conducted at PTRM Sandat Sanglah Hospital in August to October 2015 using a descriptive cross-sectional design.Results: The results of this study showed 100% of respondents smoked at a young age with 76% of respondents having a daily smoking status. The data obtained showed that the majority of smoking clients in the age of 13-15 years were 56% and 42% smoked at 16-19 years old. Judging from alcohol consumption, all study respondents consumed alcohol and 74% of respondents consumed marijuana. Of the total respondents, 60% consumed benzodiazepine and 62% of respondents took amphetamines. As many as 66% of respondents took halucinogen drugs and were responsive who consumed opioids by 36%.Conclusion: Percentage of cigarette use in PTRM Sandat clients Sanglah Hospital one hundred percent positive using cigarettes with most having daily smoking status and all starting smoking in their teens. Smoking on PTRM Sandat clients at Sanglah General Hospital when teenagers become gateways for other drug use.